Human intestinal epithelial cells respond to β‐glucans via Dectin‐1 and Syk. Issue 12 (27th October 2014) - Cohen‐Kedar, Sarit; Baram, Liran; Elad, Hofit; Brazowski, Eli; Guzner‐Gur, Hanan; Dotan, Iris
Abstract : Intestinal epithelial cells (IECs) are the first to encounter luminal antigens and may be involved in intestinal immune responses. Fungi are important components of the intestinal microflora. The potential role of fungi, and in particular their cell wall component β‐glucan, in modulating human intestinal epithelial responses is still unclear. Here we examined whether human IECs are capable of recognizing and responding to β‐glucans, and the potential mechanisms of their activation. We show that human IECs freshly isolated from surgical specimens, and the human IEC lines HT‐29 and SW480, express the β‐glucan receptor Dectin‐1. The β‐glucan‐consisting glycans curdlan and zymosan stimulated IL‐8 and CCL2 secretion by IEC lines. This was significantly inhibited by a Dectin‐1 blockade using its soluble antagonist laminarin. Spleen tyrosine kinase (Syk), a signaling mediator of Dectin‐1 activation, is expressed in human IECs. β‐glucans and Candida albicans induced Syk phosphorylation, and Syk inhibition significantly decreased β‐glucan‐induced chemokine secretion from IECs. Thus, IECs may respond to β‐glucans by the secretion of pro‐inflammatory chemokines in a Dectin‐1‐ and Syk‐dependent pathway, via receptors and a signaling pathway described to date only for myeloid cells. These findings highlight the importance of fungi–IEC interactions in intestinal inflammation.